1998
DOI: 10.1159/000007111
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Stenotrophomonas (Xanthomonas) maltophilia: Comparative (NCCLS Criteria) Evaluation of Antimicrobial Drugs with the Agar Dilution and the Agar Disk Diffusion (Bauer-Kirby) Tests

Abstract: Ninety-six clinical isolates of Stenotrophomonas maltophilia were examined with the agar dilution method for susceptibility to 19 antimicrobial drugs. Doxycycline, cotrimoxazole, timentin, ofloxacin, fosfomycin, and piperacillin + tazobactam, in that order, inhibited the majority of strains. All isolates were resistant to nitrofurantoin. Concurrent disk susceptibility (Bauer-Kirby method) testing, using currently valid NCCLS interpretative criteria for Pseudomonas aeruginosa, uncovered a significant incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
0
20
0
3
Order By: Relevance
“…As previously reported (4), a high level of agreement among these techniques was obtained (data not shown). Trimethoprim-sulfamethoxazole resistance was detected in 26.2% of strains, which is higher than the rates (0% to 10%) previously reported (4,5,18). Different methodologies and breakpoints could be responsible for these differences.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…As previously reported (4), a high level of agreement among these techniques was obtained (data not shown). Trimethoprim-sulfamethoxazole resistance was detected in 26.2% of strains, which is higher than the rates (0% to 10%) previously reported (4,5,18). Different methodologies and breakpoints could be responsible for these differences.…”
mentioning
confidence: 58%
“…On the other hand, independent studies have demonstrated methodological problems associated with susceptibility testing of S. maltophilia (4,6,7,18). In our study, in the absence of specific NCCLS recommendations for S. maltophilia, the agar dilution technique was used, but MICs were read after a full 24-h incubation at 35°C (13).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Levofloxacin has been reported to exert good in vitro activity on S. maltophilia (3,15); nevertheless, the observed percentages of ciprofloxacin-susceptible (58.9%) and intermediate (18.5%) strains were high between the two studies (3,15). Such a result is probably due to assay variations (14,16). S. epidermidis isolates were more susceptible to levofloxacin than ciprofloxacin, mainly when they were oxa-R, as described by Cafiso et al (4), who found levofloxacin to exert 30% more activity than ciprofloxacin on oxa-R coagulasenegative staphylococci.…”
mentioning
confidence: 99%
“…Antibiotic susceptibility to ampicillin, apramycin, chloramphenicol, ciprofloxacin, carbenicillin, cephalothin, erythromycin, gentamicin, imipenem, kanamycin, naladixic acid, rifampin, sulfisoxazole, streptomycin, tetracycline, trimethroprin, trimethroprim-sulfamethoxazole, and norfloxacin was determined by the BauerKirby antibiotic disk diffusion method, which was performed according to the recommendations of the National Committee for Clinical Laboratory Standards using Mueller-Hinton agar (Difco) containing 1% NaCl (47,65).…”
Section: Methodsmentioning
confidence: 99%